2021
DOI: 10.2147/cia.s316064
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Race May Explain Differential Burden of White Matter Hyperintensity Load

Abstract: Compared to European Americans, research indicates that African Americans have higher white matter hyperintensity (WMH) load; however, the clinical and biological bases underlying this higher burden are poorly understood. We hypothesize that obesity may explain differences in WMH between African and European Americans. Methods: Participants enrolled in longitudinal brain aging studies (n=292; 61% Female; 92% European American; mean age=69.6±7.7) completed evaluations including medical exams, neuroimaging, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…While our results do demonstrate a higher proportion of Black/African Americans having at least one APOE-e4 allele (44.4% vs. 40.4%), they also demonstrate that the presence of an APOE-e4 allele was associated with WMH and Hippocampal volume, but not cognitive status in Black/African Americans in our sample. These results add to the literature that posits differential associations with WMH being the driver of disparate WMH burden seen by race ( Seixas et al, 2021 ), especially since no significant differences were seen in WMH burden across race in this sample. However, given the fact that we did not conduct analyses subdivided by cognitive status, caution must be taken with inferences related to the results surrounding cognitive status.…”
Section: Discussionsupporting
confidence: 71%
“…While our results do demonstrate a higher proportion of Black/African Americans having at least one APOE-e4 allele (44.4% vs. 40.4%), they also demonstrate that the presence of an APOE-e4 allele was associated with WMH and Hippocampal volume, but not cognitive status in Black/African Americans in our sample. These results add to the literature that posits differential associations with WMH being the driver of disparate WMH burden seen by race ( Seixas et al, 2021 ), especially since no significant differences were seen in WMH burden across race in this sample. However, given the fact that we did not conduct analyses subdivided by cognitive status, caution must be taken with inferences related to the results surrounding cognitive status.…”
Section: Discussionsupporting
confidence: 71%
“…246 In another study, obesity was found to significantly increase the risk of WMH in African Americans. 247 These findings indicate that obesity is associated with LA severity and that it could be involved in the pathogenesis of LA. Another recent study showed that visceral obesity contributed to a higher DWMH/PVWMH ratio through elevated levels of the pro-inflammatory cytokine interleukin-6, independent of age and sex, thus providing insights into the possible inflammatory mechanisms underlying DWMLs, 245 although future studies are required to confirm this hypothesis at the molecular level and using imaging assessment and animal models.…”
Section: Obesitymentioning
confidence: 74%
“…69,125,245 Recently, the association between obesity and LA was shown to depend on sex and race. 246,247 In one study, there were significant differences between men and women in terms of the association between BMI and DWMH; moreover, only male sex interacted with higher BMI to result in increased DWMH volume. 246 In another study, obesity was found to significantly increase the risk of WMH in African Americans.…”
Section: Obesitymentioning
confidence: 97%
“…The prevalence of WMH differs between populations, wherein WMH frequently observed in older populations. Seixas et al demonstrated that the prevalence of WMH was 95.8% among healthy individuals (age: 65.1 ± 8.2 years) [ 10 ]. Another study reported that the prevalence of WMH was 56% in healthy individuals (age: 16–78 years) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%